Pola pelayanan keluarga berencana pada masa pandemi COVID-19 dan strategi menghadapi new normal di Yogyakarta - Fitriani Mediastuti; Sri Sugiharti; Istri Bartini; Aji nugroho (Jurnal Kependudukan Indonesia, 2022)
This study aims to determine the patterns of family planning services during the pandemic and the providers' strategies in facing the new normal in the Special Region of Yogyakarta (DIY). This research uses a mixed method with a sequential explanatory design. This study found that the pattern of family planning services in DIY experienced changes when the COVID-19 pandemic occurred. Changes occurred in contraceptive coverage, types of contraception, methods, counselling behaviour and distribution of respondents serving family planning. Several providers have also conducted counselling through online media to increase family planning in the new normal period. However, they have not been able to solve the problem of family planning acceptors. The new family planning service strategy must pay attention to health protocols to minimize the risk of being infected with COVID-19 and increase the coverage of family planning acceptors. Therefore, a strategy is needed to realize the commitment and creativity of providers to improve the quality of counselling services through online media and provide services following health protocols in the era of the new normal.